The Du Pont System in Measuring Financial Performance in The Food and Beverage Company Sub-Sector - Kurniawati, Nanda; Mahsina, Mahsina; Masyhad, Mashyad (Equity: Jurnal Akuntansi, 2024)
This study aims to determine the assessment of financial performance in the food and beverage company sub-sector listed on the IDX for the 2020-2023 period using the du pont system analysis This research is descriptive research with a qualitative approach. The approach in this study uses a comprehensive du pont system financial ratio. The results of this study indicate that the Du Pont System analysis in the food and beverage company sub-sector for the 2020-2023 period has poor financial performance because the ROE and ROI values fluctuate. Based on the results of the ratio using the du pont system analysis, the comparison of the financial performance of the food and beverage company sub-sector for the 2020-2023 period calculated using NPM, TATO, EM, ROI, ROE ate the best results at PT Multi Bintang Indonesia Tbk. While the year that has poor financial performance is at PT Sentra Food Indonesia Tbk.